Impacts of a changing earth on microbial dynamics and human health risks in the continuum between beach water and sand. (1st October 2019) - Weiskerger, Chelsea J.; Brandão, João; Ahmed, Warish; Aslan, Asli; Avolio, Lindsay; Badgley, Brian D.; Boehm, Alexandria B.; Edge, Thomas A.; Fleisher, Jay M.; Heaney, Christopher D.; Jordao, Luisa; Kinzelman, Julie L.; et al.
Abstract: Although infectious disease risk from recreational exposure to waterborne pathogens has been an active area of research for decades, beach sand is a relatively unexplored habitat for the persistence of pathogens and fecal indicator bacteria (FIB). Beach sand, biofilms, and water all present unique advantages and challenges to pathogen introduction, growth, and persistence. These dynamics are further complicated by continuous exchange between sand and water habitats. Models of FIB and pathogen fate and transport at beaches can help predict the risk of infectious disease from beach use, but knowledge gaps with respect to decay and growth rates of pathogens in beach habitats impede robust modeling. Climatic variability adds further complexity to predictive modeling because extreme weather events, warming water, and sea level change may increase human exposure to waterborne pathogens and alter relationships between FIB and pathogens. In addition, population growth and urbanization will exacerbate contamination events and increase the potential for human exposure. The cumulative effects of anthropogenic changes will alter microbial population dynamics in beach habitats and the assumptions and relationships used in quantitative microbial risk assessment (QMRA) and process-based models. Here, we review our current understanding of microbial populations and transport dynamics across the sand-water continuum at beaches, how these dynamics can be modeled, and how global change factors (e.g., climate and land use) should be integrated into more accurate beachscape-based models. Graphical abstract: Image 1 Highlights: Beaches are dynamic mosaics of aquatic, sand, and sediment ecosystems. The sand-water continuum plays an important role in beach microbial contamination. Climate change may alter contaminant dynamics in sand, affecting public health. Hydrodynamic modeling can characterize microbial dynamics in sand and water. Beach management policy lags behind research into sand as a contamination source.